2022
DOI: 10.33448/rsd-v11i11.33585
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective of urolithiasis in dogs and cats at the Veterinary Hospital University Brazil – Fernandópolis/State of São Paulo between January 2018 and April 2019

Abstract: Urolithiasis is a disorder characterized by the presence of stones in the urinary tract, associated with multifactorial causes. It is frequent in small animals. The objective of the present study is to formulate a profile of the patients affected by this disease and contribute to more accurate diagnoses and more effective therapies, aiming to reduce reoccurrences so common to this disease. The study was carried out via the exploratory analysis of the medical records of patients diagnosed with urolithiasis at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(33 reference statements)
0
0
0
Order By: Relevance
“…This is in line with a study reported by Suryani (2015) where as many as 88% of cats diagnosed with urolithiasis were male in Surabaya, Indonesia. The same study was also reported by Brilhante et al (2022) in Brazil where 75% of cats were male during 20182019 period.…”
Section: Resultssupporting
confidence: 83%
“…This is in line with a study reported by Suryani (2015) where as many as 88% of cats diagnosed with urolithiasis were male in Surabaya, Indonesia. The same study was also reported by Brilhante et al (2022) in Brazil where 75% of cats were male during 20182019 period.…”
Section: Resultssupporting
confidence: 83%